"Humbug" or "Human Good?": E.P. Thompson, the Rule of Law and Coercive Labor Relations Under Neoliberal American Capitalism. (20th April 2015) - Clark, Gabrielle
Abstract: E.P. Thompson maintained a steady ambivalence toward "the rule of law" in the context of early modern England, famously calling it, in Whigs and Hunters, both "humbug" and an "an unqualified human good." Working-class people, Thompson claimed, could gain or lose ground through the legal system, as anywhere else; they could make use of the state, and embed their victories into its juridical structure, as well as be crushed by it. In this article, I argue that Thompson's perspective serves us well in understanding legal struggles and outcomes over the terms of coerced labor, longstanding under liberal American capitalism, yet, increasingly brought into the market, privatized, or expanded in the neoliberal United States. I describe this process as the dialectic between repression, competing systems of rights, and change across a number of examples: the emergence of "workfare" in the 1960s and 1970s, culminating in the 1996 federal law signed by President Clinton; the privatization of the modern prison, and, forced labor within it; state control over deportable labor; and the legal regime underlying globalized production—e.g., the denial of legal standing to workers abroad to sue American interests. In each case, I note how there has been pressure exerted "from the bottom up, " as workers have engaged discourses of formal equality and norms of liberalism to make claims on a legal regime that violates such principles even as it becomes increasingly part of market processes. Neoliberalism comes into view as an amalgam of legal coercion and a struggle over rights—the Janus face of the law described by Thompson—under conditions of market-based change.